Aligned Carbon Nanotubes for High‐Efficiency Schottky Solar Cells. Issue 8 (6th March 2013) - Di, Jiangtao; Yong, Zhenzhong; Zheng, Xinhe; Sun, Baoquan; Li, Qingwen
Abstract The development of low‐cost and high‐efficiency silicon Schottky solar cells has drawn considerable interest in recent years. A facial approach for the fabrication of carbon nanotube–silicon (CNT–Si) Schottky solar cells by using aligned double‐walled CNTs drawn from a CNT array is demonstrated. The aligned CNTs help to form high CNT–Si junction density and provide efficient charge‐transport paths. The power conversion efficiency (PCE) reaches 10.5%, which is higher than that of solar cells fabricated using pristine and random CNT networks. Furthermore, the cell fabrication is scalable, and the solar cells fabricated in one batch show very small PCE fluctuations.